(untitled) (Scientific journal of the Fergana State University, 2023)
The article is devoted to the analyses of the works by Shukurullo, dedicated to the theme of repression, in particular, “Buried without shroud”, “Living spirits” and “Trunk of jewels”. The writer’s artistic skills on the creation of the typical characters have been studied.